2021
DOI: 10.3390/s21227548
|View full text |Cite
|
Sign up to set email alerts
|

Hip Lift Transfer Assistive System for Reducing Burden on Caregiver’s Waist

Abstract: In Japan, the aging population is expected to increase the number of elderly people in the future. The purpose of this study was to develop a hip lift transfer assistive system to improve the QOL of elderly living and to prevent back pain for caregivers. We extracted the impediment factor and the necessary scene for the assistance, decided on the transfer process from the wheelchair in the toilet, and considered the reduction method of the burden based on the quantitative evaluation of the caregiver’s lumbar b… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
6
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
2
2
1

Relationship

1
4

Authors

Journals

citations
Cited by 6 publications
(6 citation statements)
references
References 15 publications
0
6
0
Order By: Relevance
“…In previous study, we identified the constraints and requirements for a device adapted to the environment of elderly care facilities. We conducted a quantitative assessment of the burden of caregivers' transfer movements, extracted functional requirements for reducing lumbar burden based on the assessment, and explored specifications for the transfer assistive device [16].…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…In previous study, we identified the constraints and requirements for a device adapted to the environment of elderly care facilities. We conducted a quantitative assessment of the burden of caregivers' transfer movements, extracted functional requirements for reducing lumbar burden based on the assessment, and explored specifications for the transfer assistive device [16].…”
Section: Discussionmentioning
confidence: 99%
“…Subsequently, by utilizing a three-dimensional motion measurement device, we quantitatively assessed the transfer movements of caregivers, extracting equipment requirements to alleviate the lower back burden of caregivers. The equipment specifications, as illustrated in Figure 1, are reported in [16].…”
Section: Positioning Of Existing Research and This Researchmentioning
confidence: 99%
See 2 more Smart Citations
“…Assisting in transferring can cause back pain in caregivers, and reduced transferring ability significantly increases caregiver burden [21][22][23]. Various welfare interventions have been developed to reduce caregiver burden for transferring [24]. In addition, many daily life situations, such as toileting, bathing, and going out, involve transferring, which can affect nursing care in general.…”
Section: Plos Onementioning
confidence: 99%